Field geophysics - Milsom, John 1939- (Wiley, 2011)
This handy pocket-sized field guide provides practical information and assistance to anyone engaged in small-scale surveys on the ground. Fully revised and updated throughout, the Fourth Edition includes comprehensive updates on the use of GPR and GPS and new sections on surface wave seismics and towed array systems. This has become the standard text in this area for use in the field and the experience of the two authors will ensure the book retains its place as one of the most popular handbooks in applied geophysics. * Fully revised and updated to incorporate new developments in the field; * Focus on quality control of the acquisition of data and basic field interpretation; * User-friendly, accessible writing style; * Includes updates on Ground Penetrating Radar and the use of GPS; * New section on surface wave methods.
Keywords: Geophysik; Prospektion; Angewandte Geophysik; Methode; Einführung